FAKTOR-FAKTOR YANG MEMPENGARUHI KEKALAHAN M.AMIN DAN M. SHALEH DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI KAMPAR PERIODE 2017-2022 - Amri, Husni; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Elections are the means to carry out the people's sovereignty is based on the principle of direct, public, free and confidential, and honest and fair. Political stability is essential to facilitate the implementation of development, a safe, fair, and open election process. The result of voting by all citizens, which is expected to deliver the nation to a clean and authoritative, peaceful and prosperous government. Couples M. Amin and M. Shaleh is one of the candidate pairs who participated in the election of Kampar Regency Head of 2017-2022 period who got the sequence one. However, in the election of the head of the region M. Amin and M. Shaleh lost and only got the order to 4 out of five pairs of candidates who participated in the election. However, the defeat suffered by M. Amin and M. Shaleh is not the end of any struggle in helping and building up of Kampar Regency society. let alone M. Amin known by a successful entrepreneur and also served as chairman of Apindo (Indonesian Employers Association) Kampar regency. of course M. Amin has an important role in economic affairs in Kampar. The base of support consists of the basis of political parties, cultural bases and social bases and also diliat from political strategy that is political communication, political marketing and the capability of successful teams with the aim to win the couple M.Amin and M, Shaleh not run optimally.Keywords: Defeat factor, base off support, successful team capabilities